Aleksey Khomyakov: Arsitek Pembaruan Ortodoks dan Pemikiran Rusia - Kuznetsov, Michael (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2026)
This study explores the intellectual legacy of Aleksey Stepanovich Khomyakov (1804–1860), a foundational thinker in 19th-century Russian Orthodox theology whose concept of sobornost'—communal unity in freedom and love—critiqued Western rationalism and individualism. The background highlights the historical tensions between Eastern Orthodox communal spirituality and Western individualistic traditions amid Russia's modernization. The objective is to analyze how Khomyakov's lay theology, rooted in Orthodox bogoslovie, reinterprets patristic sources to address modern fragmentation and proposes Russia as a messianic Third Rome. Employing hermeneutic and comparative textual analysis of Khomyakov’s primary works (e.g., “The Church is One”) alongside their reception in 20th–21st century scholarship (Lossky, Berdyaev, Florovsky, Zenkovsky), the study demonstrates that his synthesis of vita contemplativa and activa democratized religious discourse. The findings reveal sobornost' as a blueprint for societal wholeness through love-driven unity, offering insights for contemporary interdisciplinary religious studies. In conclusion, Khomyakov’s thought provides a valuable corrective to modern social alienation and fragmentation. This study contributes to enriching the study of communal theology by presenting a conceptual reinterpretation of sobornost as an alternative paradigm to modern individualism through an examination of Khomyakov's thought in interpreting the contemporary crisis of social solidarity. Furthermore, this study offers a new conceptual framework for global religious studies in understanding the relationship between spirituality, community, and collective identity in the modern era.